Soil Moisture Response to Short-Term Inorganic Fertilization on Tef (Eragrostis tef (Zucc.) Trotter) Crop Varieties in Northern Ethiopia - Gebreyesus Brhane Tesfahunegn (Applied and Environmental Soil Science)
Little is known about soil nutrient practice effects on soil moisture under cereal cropping systems. The objective of this research was to evaluate soil moisture content (SMC) response to short-term nitrogen (N) and phosphorus (P) fertilizer rates applied on tef crop varieties and their interactions. A rain-fed fertilizer experiment using tef varieties as the test crop was conducted for two years (2012-2013) in the Chromic Cambisols of northern Ethiopia. The experimental design was laid down in randomized complete block design with three replications. Two treatment factors, namely, fertilizer (four N + P rates) and variety (three tef varieties), were tested. Soil samples were taken at different tef crop growth stages or days after sowing time (DAS) to determine SMC using the gravimetric method. Data were analyzed at a probability level of 0.05. The fertilizer treatments significantly affected the SMC determined at the different tef growth stages and cropping seasons. The highest SMC was determined at 33 DAS (51 m3·m−3), but SMC decreased with increasing fertilizer rates. A higher SMC response to local tef variety than improved variety was found across all the growth stages and cropping seasons. There were also significant differences in SMC among the treatment interactions determined at the different growth stages and across the years. The paired mean differences in SMC due to the treatments between the two years were strongly correlated (r > 0.90, P=0.001). For SMC response being effective to fertilizer and its interaction effect with variety, it is suggested that soil management practices that improve moisture such as organic sources should be integrated with the inorganic fertilizer in the conditions of Chromic Cambisols in northern Ethiopia.